2020
DOI: 10.1016/j.conbuildmat.2020.118514
|View full text |Cite
|
Sign up to set email alerts
|

Wet casting of multiple mix horizontally layered concrete elements

Abstract: Functionally graded concrete, where multiple mixes are layered in structural elements, is a promising technology for minimising cement use. However, a challenge when fabricating weton-wet graded concrete is the control of the fresh state deformations of multiple mixes cast into the same mould. Horizontally cast elements with two different concrete mix layers were investigated to ascertain the influence of mix density, workability and layer sequence on the intended material placement. Horizontal layers were ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Since the SCM mixture had a much lower viscosity and fresh unit weight compared to the UHPC, it could not resist the weight of UHPC as a separate layer in case a UHPC mixture with a stiff plastic consistency was poured on it. A similar issue was also reported in a previous study [21].…”
Section: Evaluation Of Production Techniquesupporting
confidence: 89%
“…Since the SCM mixture had a much lower viscosity and fresh unit weight compared to the UHPC, it could not resist the weight of UHPC as a separate layer in case a UHPC mixture with a stiff plastic consistency was poured on it. A similar issue was also reported in a previous study [21].…”
Section: Evaluation Of Production Techniquesupporting
confidence: 89%
“…Studies [ 40 , 41 , 42 ] showed that horizontally layered FGC elements with a short delay time (20–60 min) between the deposition of each concrete mix layer could be fabricated. A slight delay (at least 20 min) enables the base layer to have some degree of a thixotropic structure before receiving the concrete layer on top, ensuring that the ideal hardened layer geometry is achieved [ 29 ]. Andre et al [ 29 ] observed that concerning the expected deviation from a horizontal interface between mixes, the combination of the lower layer mixture (the highest density and the lowest fluidity) and the upper layer mixture (the lowest density and the highest fluidity) is likely the best-case scenario.…”
Section: Resultsmentioning
confidence: 99%
“…A slight delay (at least 20 min) enables the base layer to have some degree of a thixotropic structure before receiving the concrete layer on top, ensuring that the ideal hardened layer geometry is achieved [ 29 ]. Andre et al [ 29 ] observed that concerning the expected deviation from a horizontal interface between mixes, the combination of the lower layer mixture (the highest density and the lowest fluidity) and the upper layer mixture (the lowest density and the highest fluidity) is likely the best-case scenario. For sample L12T50 in this study, the fluidity of the top layer was significantly higher than that of the bottom layer, which hydrated for 50 min, although the densities of the two layers were almost equal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The target slump is 10-30 mm (slump class S1 in EN 206 [7]). This slump value was chosen since the layer stability in fresh-on-fresh cast FGC was found to be favourable for mixes of higher stiffness [25]. Furthermore, it is assumed that workability requirements for all mixes are constant for the study to be comparative (i.e.…”
Section: Virtual MIX Compositionmentioning
confidence: 99%